Evaluation of Streptococcus mutans Adhesion to Stainless Steel Surfaces Modified Using Different Topographies Following a Biomimetic Approach (2021)
Abstract: Bacterial adhesion to surfaces is the first step in biofilm formation, which leads to the development of conditions that may compromise the health status of patients. Surface modification has been proposed to reduce bacterial adhesion to biomaterials. The objective of this work was to assess and compare Streptococcus mutans adhesion to the surface of biomimetically-modified stainless steel using different topographies. Stainless steel plates were modified using a soft lithography technique following a biomimetic approach. The leaves from Colocasia esculenta, Crocosmia aurea and Salvinia molesta were used as surface models. Silica sol was synthesized using the sol-gel method. Following a soft lithography technique, the surface of the leaves were transferred to the surface of the SS plates. Natural and modified surfaces were characterized by means of atomic force microscopy and contact angle. Streptococcus mutans was used to assess bacterial adhesion. Contact angle measurements showed that natural leaves are highly hydrophobic, but such hydrophobicity could not be transferred to the metallic plates. Roughness varied among the leaves and increased after transference for C. esculenta and decreased for C. aurea. In general, two of the surface models used in this investigation showed positive results for reduction of bacterial adhesion (C. aurea and C. esculenta), while the other showed an increase in bacterial adhesion (S. molesta). Therefore, since a biomimetic approach using natural surfaces showed opposite results, careful selection of the surface model needs to be taken into consideration.